PENGARUH PENGELOMPOKAN SISWA BERDASARKAN KEMAMPUAN PADA PEMBUATAN PROYEK MINIATUR JEMBATAN - Erine Trisnasari Ine (Jurnal Genta Mulia, 2025)
This study aims to determine the effect of grouping students based on ability in the project of making miniature bridge projects for students in grades XI-3 and XI-4 of SMA Negeri 2 Ponorogo. The study uses an interview method with questions about students' motivation and experiences during the making of miniature bridge projects. The data obtained are qualitative then analyzed using descriptive analysis techniques. The results of the study indicate that grouping students based on ability in making miniature bridge projects mostly has a positive impact, encouraging students to be actively involved in the completion. The author analyzes students' responses to grouping based on ability in making miniature bridges.